2022
DOI: 10.1155/2022/5069918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pamidronate Disodium Combined with Calcium on BMD Values and Severity of Pain in Elderly Patients with Osteoporosis Based on Mobile Terminal Platform for Internet of Things

Abstract: Objective. To explore the effects of pamidronate disodium combined with calcium on BMD values and the severity of pain in elderly patients with osteoporosis based on the mobile terminal platform for the Internet of Things. Methods. The data of 120 patients admitted to our hospital from January 2019 to December 2020 were retrospectively analyzed. According to the patients’ condition and medication wills, they were divided into the experimental group ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Likewise, with a 4-month treatment in 19 patients, alendronate (5 mg/day), but not alfacalcidol, improved pain intensity (VAS) and pain-related QOL (Kawate et al, 2010). In a recent retrospective study pamidronate induced lower pain score than alendronate (p < 0.001) (Bai et al, 2022). A real-life study in patients after vertebroplasty showed that surgery combined with alendronate or zoledronate improved pain relief with less disability (p < 0.05) (Qian et al, 2022).…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…Likewise, with a 4-month treatment in 19 patients, alendronate (5 mg/day), but not alfacalcidol, improved pain intensity (VAS) and pain-related QOL (Kawate et al, 2010). In a recent retrospective study pamidronate induced lower pain score than alendronate (p < 0.001) (Bai et al, 2022). A real-life study in patients after vertebroplasty showed that surgery combined with alendronate or zoledronate improved pain relief with less disability (p < 0.05) (Qian et al, 2022).…”
Section: Bisphosphonatesmentioning
confidence: 99%